The co-inhibitory receptor TIGIT regulates NK cell function and is upregulated in human intrahepatic CD56bright NK cells - Annerose E. Ziegler; Annerose E. Ziegler; Pia Fittje; Luisa M. Müller; Annika E. Ahrenstorf; Kerri Hagemann; Sven H. Hagen; Leonard U. Hess; Annika Niehrs; Tobias Poch; Gevitha Ravichandran; Sebastian M. Löbl; et al. (Frontiers in Immunology, 2023)
The crosstalk between NK cells and their surrounding environment is enabled through activating and inhibitory receptors, which tightly control NK cell activity. The co-inhibitory receptor TIGIT decreases NK cell cytotoxicity and is involved in NK cell exhaustion, but has also been associated with liver regeneration, highlighting that the contribution of human intrahepatic CD56bright NK cells in regulating tissue homeostasis remains incompletely understood. A targeted single-cell mRNA analysis revealed distinct transcriptional differences between matched human peripheral blood and intrahepatic CD56bright NK cells. Multiparameter flow cytometry identified a cluster of intrahepatic NK cells with overlapping high expression of CD56, CD69, CXCR6, TIGIT and CD96. Intrahepatic CD56bright NK cells also expressed significantly higher protein surface levels of TIGIT, and significantly lower levels of DNAM-1 compared to matched peripheral blood CD56bright NK cells. TIGIT+ CD56bright NK cells showed diminished degranulation and TNF-α production following stimulation. Co-incubation of peripheral blood CD56bright NK cells with human hepatoma cells or primary human hepatocyte organoids resulted in migration of NK cells into hepatocyte organoids and upregulation of TIGIT and downregulation of DNAM-1 expression, in line with the phenotype of intrahepatic CD56bright NK cells. Intrahepatic CD56bright NK cells represent a transcriptionally, phenotypically, and functionally distinct population of NK cells that expresses higher levels of TIGIT and lower levels of DNAM-1 than matched peripheral blood CD56bright NK cells. Increased expression of inhibitory receptors by NK cells within the liver environment can contribute to tissue homeostasis and reduction of liver inflammation.